Analisis kualitas daya pada instalasi listrik Politeknik Negeri Samarinda - Khairuddin Karim; Rusda Rusda; Masing Masing (Seminar Nasional LP2M UNM, 2019)
The purpose of this study is to determine Power Quality at Samarinda State Polytechnic Electrical Installation. Measures of power quality include voltage and current imbalances, harmonics, power factors, voltage dip / swell and sag, and flicker. The research location was the Samarinda State Polytechnic Campus. The research was conducted by conducting direct measurements using a Power Quality Analyzer and the measurement results were compared with existing standards such as the IEEE-519 standard or the NEMA standard ((National Equipment Manufacturer's Association) about voltage imbalances. Data retrieval is done by direct measurement on installation panels in several units such as Distribution Substation, Building Directorate, Electrical Engineering Laboratory, Computer Laboratory, Machine Workshop, and Electrical Workshop. The measurement results show that voltage / current fluctuations occur but are still within the permissible limits, ranging from 228 to 242 Volt. The imbalance of voltage is still below 2% and this still meets the permitted standard. While the harmonic content still meets the standards, which is still below 5%, which is only around 2.4%. To measure overall quality, data is obtained from measurements on Distribution Station Panel on side s secondary from 20kV / 380V TM Transformer 555KVA and from TM 20kV / 380 Transformer 159 kVA. Measurements are carried out for approximately 1 day 24 hours starting at around 5:00 p.m. until 5 p.m. in the following afternoon.